Poly(ester-ether)s: III. assessment of cell behaviour on nanofibrous scaffolds of PCL, PLLA and PDX blended with amorphous PMeDX. Issue 4 (1st December 2014) - Goonoo, N.; Bhaw-Luximon, A.; Rodriguez, I. A.; Wesner, D.; Schönherr, H.; Bowlin, G. L.; Jhurry, D.
Abstract : SEM images of HDF cells on scaffolds: (a) PCL/PMeDX: 93/7-good adhesion and proliferation, (b) PDX/PMeDX: 98/2-good adhesion, proliferation & infiltration and (c) PLLA/PMeDX: 85/15-good proliferation and infiltration. Abstract : The aim of this paper is to investigate the physico-chemical properties, degradation behaviour and cellular response of electrospun fibre-scaffolds of semi-crystalline PCL, PLLA and PDX blended with amorphous poly(methyl dioxanone) (PMeDX). Electrospun PCL/PMeDX and PLLA/PMeDX blend mats in varying weight ratios of the two components were fabricated and their overall performance was compared with similar composition PDX/PMeDX scaffolds. DSC analysis showed almost no change in crystallization temperature of PCL with increasing PMeDX content and TGA showed a different degradation profile as PMeDX content increased. The appearance of two crystallization peaks for PLLA/PMeDX blends suggested stereocomplex formation. As noted from AFM images, addition of PMeDX caused a change in the width of the lamellae from 14.8 ± 2.9 nm in 100/0 mat to 32.0 ± 11.5 nm in 85/15 mat. Moreover, PCL/PMeDX blend mats show a significant drop in Young's modulus for 93/7, 90/10 and 85/15 compositions compared to 100/0 and 98/2. On the other hand, no clear trend in mechanical properties was observed for espun PLLA/PMeDX mats with increasing PMeDX content. Based on these analyses, it was concluded that PCL and PMeDX were immiscible while miscible blends were obtained with PLLA and PMeDX. Initial degradation of electrospun mats over a period of 5 weeks appears to occur via a surface erosion mechanism. In vitro cell culture studies using HDFs showed that the scaffolds were bioactive and a greater density of viable cells was noted on electrospun PCL/PMeDX and PLLA/PMeDX scaffolds compared to PCL and PLLA mats respectively. HDFs infiltrated through the entire thickness of espun 85/15 PLLA/PMeDX scaffold due to a combination of factors including morphology, porosity, surface characteristics and mechanical properties.